2001
DOI: 10.1074/jbc.m003624200
|View full text |Cite
|
Sign up to set email alerts
|

ACEII, a Novel Transcriptional Activator Involved in Regulation of Cellulase and Xylanase Genes of Trichoderma reesei

Abstract: A novel yeast-based method to isolate transcriptional activators was applied to clone regulators binding to the cellulase promoter cbh1 of the filamentous fungus Trichoderma reesei (Hypocrea jecorina). This led to the isolation of the cellulase activator ace2 encoding for a protein belonging to the class of zinc binuclear cluster proteins found exclusively in fungi. The DNA-binding domain of ACEII was expressed as a glutathione S-transferase fusion protein in Escherichia coli, and ACEII was shown to bind in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
243
0
13

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 302 publications
(263 citation statements)
references
References 35 publications
7
243
0
13
Order By: Relevance
“…Expression of the cellulase genes (cbh1, cbh2, egl1, egl2, and egl5) of T. reesei QM9414 is coordinated through transcription factors (296). The genes encoding the transcriptional factors ACEI (585) and ACEII (18) were identified based on their ability to bind to the T. reesei cbh1 promoter region and subsequently their DNA sequences were determined. ACEII is homologous to XlnR (700), a transcriptional activator identified in Aspergillus niger, and ACEII also stimulates the expression of cellulase and xylanase genes.…”
Section: Molecular Biology Of Cellulase Enzymesmentioning
confidence: 99%
“…Expression of the cellulase genes (cbh1, cbh2, egl1, egl2, and egl5) of T. reesei QM9414 is coordinated through transcription factors (296). The genes encoding the transcriptional factors ACEI (585) and ACEII (18) were identified based on their ability to bind to the T. reesei cbh1 promoter region and subsequently their DNA sequences were determined. ACEII is homologous to XlnR (700), a transcriptional activator identified in Aspergillus niger, and ACEII also stimulates the expression of cellulase and xylanase genes.…”
Section: Molecular Biology Of Cellulase Enzymesmentioning
confidence: 99%
“…Further studies (Würleitner et al 2003) using in vitro as well as in vivo strategies, identified nucleotide sequences within 55 bp being essential for the binding of proteins and being responsible for the xyn2 regulation. It could be demonstrated that a protein-DNA complex related to both, basal transcription as well as induction of the xyn2 expression, consists of at least the Hap2/3/5 complex (Zeilinger et al 2001) and of Ace2 (Aro et al 2001), contacting an undecameric motif 5′-GGGTAAATTGG-3′ (XAE; xylanase-activating element). The Hap2/3/5 complex contacts the CCAAT box within this motif.…”
Section: Interplay Of Xyr1 With Specific Transcriptional Regulators Amentioning
confidence: 99%
“…In addition, more available cellulose and N content in the EP may have been the main reasons for the stimulation of cellulase production. More available cellulose was an environmental stress that induced the cellulase production (Aro et al 2001;Montoya et al 2012), and the high N content made it easier for fungal growth and cellulase synthesis.…”
Section: Enzyme Production By P Ostreatus Pl-5 In Ssf Of Ep and Cpmentioning
confidence: 99%